2007
DOI: 10.11150/kansenshogakuzasshi1970.81.387
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri Tablets Suppress Helicobacter pylori Infection

Abstract: Administration of L. reuteri Tablets [Reuterina (ERINA Co.,Inc.)] significantly decreased UBT in H. pylori-positive subjects, demonstrating that L. reuteri suppresses H. pylori urease activity and H. pylori density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Probiotics can prevent or inhibit the proliferation of pathogens, suppress production of virulence factors by pathogens, or modulate the immune response. L. reuteri is a promising therapy for the amelioration of infantile colic, alleviation of eczema, reduction of episodes of workplace illness, and suppression of H. pylori infection [3-9]. L. reuteri is considered an indigenous organism of the human gastrointestinal tract and is present on the mucosa of the gastric corpus, gastric antrum, duodenum, and ileum [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics can prevent or inhibit the proliferation of pathogens, suppress production of virulence factors by pathogens, or modulate the immune response. L. reuteri is a promising therapy for the amelioration of infantile colic, alleviation of eczema, reduction of episodes of workplace illness, and suppression of H. pylori infection [3-9]. L. reuteri is considered an indigenous organism of the human gastrointestinal tract and is present on the mucosa of the gastric corpus, gastric antrum, duodenum, and ileum [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[32] Likewise other studies also showed that it definitely suppresses the growth of H. pylori in stomach and gut. [3233] L. reuteri is found naturally in humans, however, it is not found in all individuals. Therefore dietary supplementation is needed to introduce and maintain high levels of L. reuteri in some people.…”
Section: Introductionmentioning
confidence: 90%
“…In one of the studies it was found that adding reuteri to omeprazole dramatically increased the cure rate from 0% to 60% of H. pylori infected patients compared with the use of drug alone. [32] Likewise other studies also showed that it definitely suppresses the growth of H. pylori in stomach and gut. [3233] L. reuteri is found naturally in humans, however, it is not found in all individuals.…”
Section: Introductionmentioning
confidence: 92%
“…La revisión bibliográfica se inició con la localización de una guía similar a la que pretendía-mos hacer, la Guía Clínica Canadiense para Suplementos Probióticos [7] y que permitió tener una base sobre la que formular la pregunta clínica. Para la formulación de la pregunta clínica nos hemos basado en el sistema PICO (Patient, Intervention, Comparison, Outcomes) [8]:…”
Section: Materials Y Métodosunclassified